MANAGEMENT OF IMPLEMENTATION OF PROJECT-BASED LEARNING (PJBL) AT SMPN 2 SOLOKANJERUK - Mahmudah, Siti; Anwar, Wafiq Fadhilah; Hidayatullah, M. Deni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the application of project-based learning (PJBL) at SMPN 2 Solokanjeruk. The techniques used in this research are observation, interviews, and documentation studies. This research uses a descriptive qualitative method by conducting a survey of the school concerned to obtain information, data collection, and documentation as evidence in carrying out this research. The results of this study indicate that the application of project-based learning (PJBL) at SMPN 2 Solokanjeruk is optimal because it can develop students' creativity and entrepreneurship.